Socio-economic preconditions of resort agglomerations development in the south of Russia - Oborin, Matvey S; Kozhushkina, Irina; Gvarliani, Tatyana; Ivanov, Nikolay (Worldwide hospitality and tourism themes, 2018)
Purpose This paper aims to analyze the modern problems and the main trends of development of the health-improving tourism sector in the southern part of Russia and to identify significant factors in overcoming the complex challenges related to specific socio-economic conditions in the study area. Design/methodology/approach The material that served as the basis of the study comprises statistical data from the Southern Federal District and its subjects, as well as data about the development of tourism infrastructure on the official websites of governments, Ministry of Tourism and the population of the Southern Federal District. This information was systematized from a number of perspectives, including identification of the chronology of health-improving tourism infrastructure development in the chosen territory, as well as the advantages and disadvantages in this area. Based on the results of the study, the authors also developed some recommendations to overcome existing inactive trends in the field of health tourism. Findings This paper sheds light on the understanding of the challenges and changes that took place in the resort agglomerations of the south of Russia in terms of current issues and those that must be addressed in the coming years. It was concluded that health tourism in the south of Russia has old traditions based on the natural resource potential of territories that are included in the composition of the Southern Federal District. At the same time, the authors came to the conclusion that, unfortunately, not resort agglomerations are fully utilized. Furthermore, some historic resorts were not well maintained by local authorities and have suffered more recently because of lack of investment. At present, the financial results of health resorts and others related to health-improving tourism are precarious as most operations are unprofitable, and so complex decisions are needed to address the underlying problem of resource optimization because of the important social and economic role of the cities in this region. They have special natural and resource potential and preserve traditions related to health-improving tourism. Research limitations/implications The paper provides a conceptual analysis based on limited empirical data combined with some directions for further research. Originality/value The paper attempts to reveal the impact of social, economic and geopolitical factors, both negative and positive, on the development of the health-improving tourism segment, restructuring of the Russian tourism market and the emergence of promising opportunities and new directions for development. The findings also provide insights for practitioners and researchers, and the tourism industry can draw on this analysis to guide the development of strategy, increase investment attractiveness, make more effective use of the natural resource potential and maintain pressure on government partners to provide support to tourism.